2018
DOI: 10.3389/fphar.2018.00960
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Universal Health Coverage on Life Expectancy at Birth (LEAB) and Healthy Life Expectancy (HALE): A Multi-Country Cross-Sectional Study

Abstract: Background: There are substantial differences in long term health outcomes across countries, particularly in terms of both life expectancy at birth (LEAB) and healthy life expectancy (HALE). Socio-economic status, disease prevention approaches, life style and health financing systems all influence long-term health goals such as life expectancy. Within this context, universal health coverage (UHC) is expected to influence life expectancy as a comprehensive health policy. The aim of the study is to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 50 publications
3
60
0
Order By: Relevance
“…Such findings are similar to the results of the present study. A study by Ranabhat et al from 194 countries showed that alcohol consumption was positively associated with adult mortality [75], coinciding with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Such findings are similar to the results of the present study. A study by Ranabhat et al from 194 countries showed that alcohol consumption was positively associated with adult mortality [75], coinciding with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Researchers have few concerns about the how of sustainable economic growth. Studies have shown that the economy would be sustainable after the guarantee of health service to all people (18,19). Poor enrollment and drop out in health insurance would significantly affect universal health coverage (20).…”
Section: Situation Of Low-and Middle-income Countries and Healthmentioning
confidence: 99%
“…Poor enrollment and drop out in health insurance would significantly affect universal health coverage (20). Likewise, increasing government health expenditures would contribute to quality health service and also coverage (18,21,22). Out of pocket expenditure increase catastrophic health expenditure and directly push into poverty (23,24).…”
Section: Situation Of Low-and Middle-income Countries and Healthmentioning
confidence: 99%
“…Ordinary citizens' capacity concerning the acquisition spread efficiently, but not fast to enough follow-up disproportionate rapid growth of out-of-pocket spending [17]. In the XXI century, the G7 countries invest in health more than 10 percent of current health expenditure [18], along with energy and infrastructure [19]. In contrast, the EM7 countries have invested in health less than five percent of current health expenditure [20] and set priority to infrastructure and the economic growth.…”
Section: Discussionmentioning
confidence: 99%